Emigration and democracy - Frédéric Docquier; Elisabetta Lodigiani; Hillel Rapoport; Maurice Schiff (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
International migration is an important determinant of institutions, not considered so far in the development literature. Using cross-sectional and panel estimation for a large sample of developing countries, we find that openness to emigration (as measured by the natives' average emigration rate) has a positive effect on home-country institutional development (as measured by standard democracy indices). The results are robust to a wide range of specifications and identification methods. Remarkably, the cross-sectional estimates are fully in line with the implied long-run relationship from dynamic panel regressions.Keywords: Migration; Institutions; Democracy; Development.
Keywords: O15; O43; F22; 330; migration; institutions; democracy; Development